PERAN KOPERASI SERBA USAHA “KELUARGA SEJAHTERA” DALAM MENSEJAHTERAKAN MASYARAKAT DI DESA PALUH KARAU HAMPARAN PERAK DAN MENGATASI PERMASALAHANNYA - Ripho Delzy Perkasa; Ryan Maulana Siregar; Muhammad Juliansyah (Jurnal Manajemen Dirgantara, 2024)
The "Prosperous Family" Multi-Business Cooperative carries out a savings and loan program with the main aim of helping its members overcome financial difficulties and improving the lives of the people in Paluh Kurau village. However, a number of problems emerged which resulted in obstacles in the operation of this prosperous family business cooperative. This research aims to (1) improve the welfare of cooperative members in Paluh Kurau village. (2) As well as providing relief to families who are less prosperous in financial terms, so that middle and lower middle class people in Paluh Kurau village can take part in the program. Because with this cooperative, the community will be helped more with financial problems that occur in a family. The research subjects we interviewed were (1) chairman (2) secretary (3) treasurer, who were located in the village of Paluh Kurau, Tanjung Perak. The data analysis technique for this research is qualitative data analysis which presents data starting from reviewing all the information collected and describing and interpreting information received from informants in the field. The results of this research show what factors cause problems in the "Keluarga Sejahtera" cooperative in running its savings and loan business, namely (1) running out of capital at the start of the cooperative's establishment (2) lack of sense of responsibility among members (3) members who are more borrowing more than saving. The strategy for resolving cooperative problems is to: (1) the management makes an agreement with cooperative members and regulations if there is indiscipline within the cooperative. (2) Resolve things wisely as a family. The conclusion that researchers got from this research is to find out what roles and problems occur in the prosperous family cooperative and how to overcome the problems that occur in the prosperous family cooperative.